2021
DOI: 10.29166/quimica.v7i1.2921
|View full text |Cite
|
Sign up to set email alerts
|

Aislamiento de Salmonella spp. en heces de fauna urbana en un parque recreativo de Quito

Abstract: La zoonosis es considerada un problema de salud pública a nivel mundial y una de las enfermedades con mayor incidencia es la salmonelosis ya que el microorganismo sobrevive a condiciones ambientales extremas y por su fácil transmisión mediante el contacto directo con animales y alimentos contaminados con materia fecal. Los reservorios zoonóticos más importantes son los perros (Canis lupus familiaris) y las palomas domésticas (Columba livia) por su cercana convivencia con el ser humano y porque excretan el pató… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In canine and domestic pigeon feces, 100 samples of canine fecal matter were collected and a percentage of 3% for Salmonella spp. was determined (Cangui et al, 2021).lThe frequency was lower than that reported in the work of Amadi and collaborators in 2018, in which fecal samples from 144 dogs were examined, of which 5.6% tested positive for Salmonella spp., (Amadi et al, 2018). Fonnegra tells us that "The presence of canine salmonellosis can vary between 1% and 18%" this is verified in the present work by obtaining a frequency of 2% (Fonnegra et al, 2009).…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…In canine and domestic pigeon feces, 100 samples of canine fecal matter were collected and a percentage of 3% for Salmonella spp. was determined (Cangui et al, 2021).lThe frequency was lower than that reported in the work of Amadi and collaborators in 2018, in which fecal samples from 144 dogs were examined, of which 5.6% tested positive for Salmonella spp., (Amadi et al, 2018). Fonnegra tells us that "The presence of canine salmonellosis can vary between 1% and 18%" this is verified in the present work by obtaining a frequency of 2% (Fonnegra et al, 2009).…”
Section: Resultsmentioning
confidence: 67%
“…It is considered of great interest to investigate the frequency of Salmonella in dogs since pets, such as dogs, can harbor Salmonella spp., asymptomatically; Because of this, estimating the frequency in dogs is difficult to establish (Dróżdż et al, 2021). Likewise, the contact between dogs and humans is daily, which could trigger complications in the health status of their owners (Cangui et al, 2019); Such is the case described in a section of this document of a child who frequently became ill with Salmonella and they could not find the source of infection. After several studies, they confirmed that their dogs were asymptomatic carriers.…”
Section: Introductionmentioning
confidence: 99%